Before and After Prohibition: Parental Communication and Modeling Associated With Emerging Adult Recreational Marijuana Attitudes and Use. Issue 3 (June 2022) - Lyons, Courtney E.; Evans, William P.; Yang, Yueran
Researchers have begun examining changes in recreational marijuana use among emerging adults (EAs), however, no studies have examined the influence of parents on EA children's marijuana use due to legalization. We sought to address this gap by using a 2019 cross-sectional online survey of 404 EA students (18–25 years; M = 20.7, SD = 1.9) about their behavioral observations and conversations with parents regarding recreational marijuana legalization in a western U.S. state. Significant increases in reports of parent communication and observed use, as well as EA attitudes and use were found post-legalization. Evaluation of two structural equation models (with configural invariance versus construct-level metric invariance) suggest that the more constrained model did not fit worse and that the relationships between parent communication and modeling are significantly related to EA attitudes and use pre- and post-legalization. Results indicate that parental socialization plays an important role in recreational marijuana attitudes and use among EA children.